The “butterfly effect” in strategic human capital: mitigating the endogeneity concern about the relationship between turnover and performance - Stern, Ithai (2022)
Research Summary: Prior literature on the relationship between the departure of strategic human capital (SHC) and firm performance is equivocal. One source of this ambiguity is the potential endogeneity: Is it the SHC departure that leads to poor firm performance, or is it poor firm performance leading to the SHC departure? We respond to repeated calls to address this issue by using the Fukushima nuclear accident in Japan as an exogenous event which triggered a “butterfly effect” that influenced the departure decisions of individuals working for firms near a nuclear plant in the United States but not the firms' performance. Our results provide strong evidence that the departure of SHC undermines firm performance, and that the effect is amplified by the strength of employee–firm relationships. Managerial Summary: This study shows that Japan's Fukushima nuclear accident prompted an increase in the departure of strategic human capital (SHC) working in firms in close proximity to nuclear plants in the United States. It provides strong empirical evidence that the departure of SHC hurts firm performance and that firms which have a strong relationship with their employees suffer more. These findings suggest a potential downside to cultivating such relationships and highlight the ripple effects of unexpected external events on firm performance.